Analysis of Supreme Court Decision Number 3507 K/PDT/2023 - Cristy, Florentina; Hadiati, Mia (Universitas Muhammadiyah Ponorogo, 2025)
The aim of this study is to investigate the authority of the Land Deed Making Officer (PPAT) in issuing Sale and Purchase Deeds Number 134/2016 and 135/2016. All actions, including legal and other acts, performed within the territory of Indonesia must adhere to the prevailing regulations and laws in the country. This requirement applies to all individuals, whether Indonesian citizens or foreign nationals currently in Indonesia. Every landowner in Indonesia is obligated to register their land in accordance with the provisions of the Basic Agrarian Law and its associated regulations, ensuring that land ownership status is clear and legally recognized, which serves as a preventive measure against disputes over land rights. This study employs a descriptive qualitative approach to examine the authority of PPAT Roy Pudyo Hermawan in executing Sale and Purchase Deeds Number 134/2016 and 135/2016. The findings indicate that the deeds were declared legally defective by the Supreme Court, as they did not satisfy the substantive legal requirements and failed to adhere to the procedural standards prescribed for deed execution by a PPAT.